Smoking Prevention, Cessation and Health Effects - Ping Wong, Li; Hoe, Victor (IntechOpen, 2019)
Smoking can lead to a variety of ongoing complications in the body, as well as long-term effects on body systems. While smoking can increase the risk of a variety of problems over several years, some of the bodily effects are immediate. This book provides a comprehensive overview of opinions and research findings on smoking and its harmful effects and serves as a valuable reference for researchers and the general public. The issue of electronic cigarettes is one of the most controversial topics in public health. This book also provides an overview of electronic cigarettes and their efficacy as smoking cessation aids. Because there is intense debate and dividing opinions about their use patterns and health concerns, up-to-date evidence of the health risks and safety of electronic cigarettes are discussed. This book also highlights the policies and regulations on electronic cigarettes that vary across countries. Lastly, readers are also enlightened on the future perspectives of electronic cigarettes and whether they are a threat or an opportunity for public health.